The Influence of Transformational Leadership on Job Satisfaction, Organizational Commitment, and Employee Performance - Atmojo, Marnis (International Research Journal of Business Studies, 2012)
This research has four main objectives; first, to prove and analyze the influence of transformational leadership towards employee job satisfaction; Second, to prove and analyze the influence of transformational leadership towards organizational commitment; Third, to prove and analyze the influence of transformational leadership towards employee performance; Fourth, to prove and analyze the influence of organization commitment towards the employee performance. This research involved 146 members of middle management as our research sample namely Head of Department, Plantation Manager, Plant Manager, Head of Bureau/Division, Head Assistant, Head of Strategic Business Unit (SBU), Chief Engineer and Head of Hospital Service. Structural Equation Modeling (SEM) was used to test and analyze relationship among the research variables. Research findings are transformational leadership significantly influences job satisfaction, transformational leadership significantly influences the organization commitment. The job satisfaction is shown to have significant influence on employee performance, and organization commitment significantly influences the employee performance.